Libya's Geopolitical Location (Political and Historical Importance) A Study in Political Geography (Comprehensive Journal of Science, 2026)
This study explores the general importance of location (political, geographical, and historical) and the importance of leveraging this location—which is usually fixed—and that the true power of a state is linked to its geographic location and its proximity to neighboring countries. It also explores the importance of this location from a natural and human perspective, and the natural and human resources that countries possess that aid their economic, political, and security advancement.Accordingly, the study area (Libya) possesses a very important geopolitical, strategic, and historical location. Its importance is further enhanced by its location on one of the most important sea areas in the world (the Mediterranean Sea). The country has also been an important link, throughout history and to this day, between neighboring Arab and African countries on the one hand, and the countries of the European continent on the other. This can be leveraged by successive political circles to achieve sustainable development for Libya .